Exohedral Addition Chemistry of the Fullerenide Anions C602− and C60⋅− - Wabra, Isabell; Holzwarth, Johannes; Hauke, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2019)

Highly Regioselective Alkylation of Hexabenzocoronenes: Fundamental Insights into the Covalent Chemistry of Graphene - Holzwarth, Johannes; Amsharov, Konstantin; Sharapa, Dmitry; Reger, David; Roshchyna, Kateryna; Lungerich, Dominik; Jux, Norbert; Hauke, Frank; Clark, Timothy; Hirsch, Andreas (Angewandte Chemie International Edition, 2017)
Keywords: alkylation; density-functional calculations; graphene; radicals; reaction mechanisms

Solvent-driven electron trapping and mass transport in reduced graphites to access perfect graphene - Vecera, Philipp; Holzwarth, Johannes; Mundloch, Udo; Edelthalhammer, Konstantin; Peterlik, Herwig; Hauke, Frank; Hirsch, Andreas (Nature Communications, 2016)
Herein, we report on a significant discovery, namely, the quantitative discharging of reduced graphite forms, such as graphite intercalation compounds, graphenide dispersions and graphenides deposited on surfaces with the simple solvent benzonitrile. Because of its comparatively low reduction potential, benzonitrile is reduced during this process to the radical anion, which exhibits a red colour and serves as a reporter molecule for the quantitative determination of negative charges on the carbon sheets. Moreover, this discovery reveals a very fundamental physical-chemical phenomenon, namely a quantitative solvent reduction induced and electrostatically driven mass transport of K + ions from the graphite intercalation compounds into the liquid. The simple treatment of dispersed graphenides suspended on silica substrates with benzonitrile leads to the clean conversion to graphene. This unprecedented procedure represents a rather mild, scalable and inexpensive method for graphene production surpassing previous wet-chemical approaches.

Synthesis, Structural Characterization, and Crystal Packing of the Elusive Pentachlorinated Azafullerene C59NCl5 - Amsharov, Konstantin; Holzwarth, Johannes; Roshchyna, Kateryna; Sharapa, Dmitry; Hampel, Frank; Hirsch, Andreas (Chemistry - A European Journal, 2017)
Keywords: azafullerene; crystal growth; halogenated fullerenes; host–guest systems; supramolecular bonding